Barriers To Regular And Continuing Participation In Higher Educational Programme As Educational Exclusion Of Scheduled Tribes In Meghalaya (Journal of Namibian Studies : History Politics Culture, 2023)
Many students are not able to continuously participate in educational programmes for various reasons such as lack of access to institutions, affordability, time constraints and life demands etc. When they are not able to continuously participate in educational programmes, some students might lose interest in studying or might not be able to compete with others. This study will examine different aspects such as distance from the college, expenditure on education, time constraints, and life demands which act as barriers to regular and continuing participation in higher educational programmes among Scheduled Tribes in Meghalaya. The descriptive survey method was used with the help of a self-made questionnaire constructed by the researcher and administered to 1026 higher education Scheduled Tribe students, and the data collected was analysed using percentages. The study found that students do not continuously participate in educational programmes because of various reasons but one of the main reasons is financial problem.